2011
DOI: 10.1074/jbc.m111.308858
|View full text |Cite
|
Sign up to set email alerts
|

Role of Scaffold Protein Afadin Dilute Domain-interacting Protein (ADIP) in Platelet-derived Growth Factor-induced Cell Movement by Activating Rac Protein through Vav2 Protein

Abstract: Background: Many signaling molecules coordinately play roles in cell movement. Results: ADIP (afadin dilute domain-interacting protein) mediates Rac activation by interacting with Vav2 for the formation of the leading edge. Conclusion: ADIP integrates the intracellular signaling to promote cell movement.Significance: This provides a new insight into the molecular mechanism of cell movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…More recently it has been shown that PDGF activates Src kinase, which in turn leads to activation of Rac31. In this context, an afadin-binding protein, afadin dilute domain-interacting protein (ADIP), interacted with Vav2, a GDP/GTP exchange factor for Rac, in a Src phosphorylation-dependent manner32. These results indicate that ADIP may be involved in PDGF-induced cell movement through Src/Rac signalling pathway and will be a potential target for α-Syn.…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been shown that PDGF activates Src kinase, which in turn leads to activation of Rac31. In this context, an afadin-binding protein, afadin dilute domain-interacting protein (ADIP), interacted with Vav2, a GDP/GTP exchange factor for Rac, in a Src phosphorylation-dependent manner32. These results indicate that ADIP may be involved in PDGF-induced cell movement through Src/Rac signalling pathway and will be a potential target for α-Syn.…”
Section: Discussionmentioning
confidence: 99%
“…Its homologous gene in rodents is ADIP (afadin DIL domain-interacting protein), the amino acid sequence of ADIP protein in mouse and rat showed 88% and 87% identity with SSX2IP protein, respectively. ADIP localized in cell-cell adherens junctions, and it can promote cell mobility by activating Rac1 through Vav2 [41], [42]. It is speculated that SSX2IP could promote cell motility, invasion and metastasis through activating Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ADIP has been shown to promote cell movement by regulating the activation of Rac1 [16]. Rac1 belongs to the Rho family and the Ras superfamily of small GTP-binding proteins, and it is an important regulator which connects membrane surface receptors and actin cytoskeleton and plays a role of molecular switch.…”
Section: Discussionmentioning
confidence: 99%
“…Cytologically, ADIP localizes at cell-cell adherens junctions and promotes cell migration by activating Rac protein through Vav2 [15,16]. All of the above characteristics are closely related to the adhesion capacity and metastatic characteristics.…”
Section: Introductionmentioning
confidence: 99%